SEKTOR UNGGULAN SUMATERA SELATAN DENGAN PENDEKATAN MODEL LOCATION QUOTIENT DAN SHIFT-SHARE - hatta, hendrixon (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2020)
Every regional government in Indonesia has increased its economic competitiveness. The regional government of South Sumatra Province attempts to increase the value of gross regional domestic product (GRDP) in each business sector and fiscal year so that it can prioritize the sector to achieve the economic improvement target. In this study, the the primary leading sectors will be ranked as a policy input to the the Government of South Sumatra Province. Leading sectors must be developed in South Sumatra to support each regional organization's program. The government policy of South Sumatra which is included in the activity programs of the regional apparatus organizations attempts to support and develop the primary leading sectors, namely, the mining and quarrying industry and the secondary sectors are the real estates and the tertiary sectors such as providing accommodation and food as well as drink that were selected in this study because it contributed to the growth significantly. Keywords: Leading Sector, GRDP, LQ, Shift-Share